Anti-inflammatory and Anti-endoplasmic reticulum stress Effects of catalpol Against myocardial ischemia-reperfusion injury in streptozotocin-induced diabetic rats - BI,FANGJIE (2020)
Abstract The current study was designed to investigate the effects and the mechanism of catalpol on myocardial ischemia-reperfusion (MI/R) injury in a diabetic rat model. Male Sprague-Dawley rats were divided into DM + sham, DM +I/R, and DM +I/R + C groups and diabetes was induced using single injections of streptozotocin (STZ; 70 mg/kg; i.p). After confirming the induction of diabetes, rats were administered physiological saline and catalpol (10 mg/kg; i.p.) daily for 28 days. Subsequently, rats were subjected to left anterior descending (LAD) coronary artery occlusion for 30 min followed by reperfusion for 2 h. Haemodynamic parameters were recorded throughout surgery, and following sacrifice, hearts were isolated for biochemical, histopathological, and molecular analyses. Catalpol treatment significantly ameliorated MI/R injury by improving cardiac function, normalizing myocardial enzyme activities and markers of oxidative stress, and by maintaining myocardial architecture. Furthermore, expression levels of the inﬂammatory cytokines TNF-α and IL-6 were decreased in biochemical and immunohistochemical studies. Additionally, the cardioprotective effects of catalpol were partly related to reductions in myocardial endoplasmic reticulum stress (ERS). In conclusion, catalpol exerts cardioprotective effects in diabetic rats by attenuating inﬂammation and inhibiting ERS.